(untitled) (Bangladesh Pharmaceutical Journal, 2015)
Wrigthia arborea (Dennst.) Mabb., locally known as Shet-kurchi, is a small deciduous tree. These species are important in the traditional healthcare, especially in menstrual and renal complaints. The present study was designed to investigate the antidiarheal and antidiabetic activities of methanol extract of W. arborea. The methanol extract was studied for antidiarrhoeal properties using castor oil and magnesium sulphate induced diarrhoeal model in mice. At the doses of 100 and 200 mg/kg body weight, the extract reduced the frequency and severity of diarrhea in test animals throughout the study period. Antidiabetic effect was also evaluated in normal and alloxan induced diabetic rats. Considerable drop of elevated blood glucose level was observed in the normoglycemic and alloxan induced diabetic rats at a dose of 150 and 300 mg/kg b.w. when the extract was given intraperitoneally. Altogether, these results suggest that the methanol extract could be used for treating diarrhea and diabetes. This is the first report of antidiarheal and antidiabetic potential of W. arborea. DOI: http://dx.doi.org/10.3329/bpj.v16i2.22306 Bangladesh Pharmaceutical Journal 16(2): 211-216, 2013